The face-to-face encounter in indigenous health care: a perspective in Lévinas - Diomedia Zacarias Teixeira; Nelson dos Santos Nunes; Rose Mary Costa Rosa Andrade Silva; Eliane Ramos Pereira; Vilza Handan
ABSTRACT Objective: To reflect on the sensitive behaviors of indigenous healthcare professionals based on the philosophy of Emmanuel Lévinas, to ratify completeness, equity, and humanity. Method: reflective study. Reflection: Studies have identified inadequacies in meeting the indigenous singularities. In the hospital and outpatient settings, they are diluted in the search for care. The difficulty of the professionals to admit them generates conflicts and non-adherence of indigenous individuals to treatments that disregard their care practices. In Lévinas, consciousness requires, "a priori," sensitivity to access the Infinity on the Face of the Other, which in the face-to-face encounters is presented to the Self as radical Alterity, proposing an Ethical relationship through transcendence. The freedom of the Self as to the Other is finite, as the Self cannot possess the Other, and infinite for its responsibility for the Other. Final considerations: The Self builds essence and existence in responsibility. In the Ethics of Alterity, in Lévinas, reflections are proposed that influence sensitive behaviors.